(untitled) (Research, Society and Development, 2022)
Microbiology is a relevant topic in the formation of any individual, as it involves basic issues of citizenship such as hygiene, environment, biotechnology, and health. However, despite its importance, the Microbiology approach is almost exclusive to the academic environment, and although it is foreseen in the Basic Education curriculum, it is often addressed in a superficial, theoretical and conceptual way. Therefore, the objective of this work was to investigate research trends in the teaching of microbiology in Brazil, aiming to understand the current strategies and discuss new ways to be taken to facilitate the learning of this subject. For this, 178 abstracts published in the “Teaching” section of the Brazilian Congress of Microbiology, from 2009 to 2021, were analyzed. The analysis of the abstracts allowed us to identify that most of these correspond to studies developed by public Higher Education Institutions, which mainly report experiences with Basic Education. The data reveal a predominantly practical teaching of Microbiology, but with the traditional curriculum, and most of the time detached from issues of social importance. Although this study reveals the commitment of many professionals to transform the teaching of Microbiology, there is still much advance to make this science accessible to all.